The Strategy of Kebonpedes District Government in Improving Quality of Public Services through the Service Innovation Program - Siti Mulya Mutiara; Dine Megawati; Andi Mulyadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The purpose of this research was to determine Kebonpedes District government's strategy in improving the quality of public services through service innovation programs. This study uses a qualitative phenomenological approach with data collection techniques of observation, interviews and documentation. Data analysis was performed by data reduction, data presentation, and conclusion/verification. The results of this study were measured by strategy indicators by Quinn (2003) showing that the Kebonpedes District Government in improving the quality of public services begins with setting steps to achieve goals based on the formulation of important issues of regional development problems and the urgency of problems that exist in district scope. Then in implementation of services, it is arranged in a directed manner in standard operating procedures designed by Kebonpedes District Government so that the public can understand the workflow of services. The program implemented by Kebonpedes District Government was created by taking into account development priorities and running a service innovation program designed to suit public needs to support an increase in the quality of public services through the Bajak Deh Ah and Layani Aja programs.